PENGARUH RECOVERY AKTIF TERHADAP PENURUNAN KELELAHAN SETELAH LATIHAN - Nimrot manalu; Amelia Febriani; Rizal Pernando Tampubolon; Pio azmi Sitompul; Muhammad Agung Firmansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Fatigue is a common physiological response that occurs after physical exercise and can reduce performance as well as hinder the body's recovery process. One method frequently used to accelerate recovery is active recovery, which involves performing low-intensity physical activity after the main exercise session. This study aimed to determine the effect of active recovery on reducing post-exercise fatigue. The research employed an experimental design involving a single group that received an active recovery treatment after completing physical exercise. Fatigue levels were measured using recovery heart rate and the Rating of Perceived Exertion (RPE) scale. The results showed that active recovery significantly reduced fatigue levels compared to the condition before treatment. Active recovery helped improve blood circulation, accelerate lactate removal, and enhance the recovery of muscle function after exercise. Therefore, active recovery can be used as an effective recovery strategy to reduce fatigue and support improvements in physical performance.